Evangelischer Kirchenbau in Bayern seit 1945 - Hübner, Hans-Peter, 1961- 1961- Herausgeber; Braun, Helmut, 1961- 1961- Herausgeber (Deutscher Kunstverlag, 2010)
More than 700 Protestant churches have been built in Bavaria since 1945. Introductory essays on the history of Protestant church architecture in Bavaria are followed by a detailed description of 58 churches and a catalogue listing the key facts about all 700 churches.